Effect of ultrasonic pre-treatment durations on the formation of zeolite-T - Wahab, I.B.M.A. (Trans Tech Publications Ltd, 2014)
In the present work, the lengthy synthesis duration of zeolite-T was successfully reduced by inducing the ultrasonic pre-treatment method prior to hydrothermal growth. The effect of ultrasonic pre-treatment durations on the formation of zeolite-T was investigated. The structure and morphology of the resultant samples were characterized by FTIR, XRD and FESEM. As verified by FTIR, samples produced using synthesis durations of 5, 4, 3 and 2 days with ultrasonic pretreatment durations of 60 min and 90 min, respectively, demonstrated zeolite-T structure. One day synthesis duration was not sufficient for the formation of zeolite-T. From the results obtained by XRD and FESEM, it was found that samples underwent 60 min ultrasonic pre-treatment produced zeolite-T with higher crystallinity, while no significant changes on the morphology of the resultant zeolite-T synthesized using ultrasonic pre-treatment durations of 60 min and 90 min. Â© 2014 Trans Tech Publications, Switzerland.